2002
DOI: 10.1038/sj.gene.6363856
|View full text |Cite
|
Sign up to set email alerts
|

Genetic determinants of rheumatoid arthritis: the inducible nitric oxide synthase (NOS2) gene promoter polymorphism

Abstract: An association study and a linkage analysis were carried out in parallel in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 20 publications
1
13
0
Order By: Relevance
“…Interestingly, in the present study we reported a different distribution of subjects carrying at least one (CCTTT) 14 allele between RRMS patients and controls, suggesting that it could exert a protective role against MS, for example by producing high levels of NO that limit the Th1 lymphocyte responses [35].…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Interestingly, in the present study we reported a different distribution of subjects carrying at least one (CCTTT) 14 allele between RRMS patients and controls, suggesting that it could exert a protective role against MS, for example by producing high levels of NO that limit the Th1 lymphocyte responses [35].…”
Section: Discussionmentioning
confidence: 93%
“…On the subject of NOS2A gene, a significant transcription effect of the highly polymorphic (CCTTT) n promoter marker has been hypothesized [34]; particularly the 14-repeat allele displayed an higher activity in the reporter gene expression when compared to the other alleles, resulting into an overproduction of iNOS in response to exogenous stimuli as viruses and bacteria [27,35]. Subjects carrying the (CCTTT) 14 allele have been reported potentially protected from autoimmune diseases like diabetes [34] and rheumatoid arthritis [35].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…An association of the number of CCTTT repeats in the NOS2A promoter with a higher risk for RA was observed previously [23,24] but no study investigated the association of this (CCTTT) n repeat with RA activity. In our study NOS2A (CCTTT) n was not significantly associated with disease activity however, the influence of NOS2A (CCTTT) n on the risk for RA was not tested.…”
Section: Discussionmentioning
confidence: 94%
“…Variations in promoter region of NOS2A have been proposed of critical importance in genetic association studies of diseases, such as severe malaria [37], rheumatoid arthritis [38], Parkinson's disease [39], inflammatory bowel disease [40] etc. These variations have collectively shown their potential in differential expression of NOS2A.…”
Section: Discussionmentioning
confidence: 99%